Método de avaliação de prontidão para implementação da Construção Enxuta - Souza, Bruno Henrique Félix de (2016)
To reduce waste and increase the generation of value for customers, more and more construction companies have sought to apply the Lean Construction. However, there is no unanimous formalization of the implementation process and companies lack information about their real capacity to go through a lean transition. As stressed by the literature, one of the key factors for the success of any lean implementation is to assess the readiness of the organization. This paper assumes that this assessment should consider the technical, human and cultural dimensions and their interrelationships. Seeking ways to evaluate, an important tool based on graph theory and matrix algebra, identified in the literature as Graph Theoretic Approach (GTA), has been applied in different contexts, with desirable properties such as the ability to model interactions between criteria and generating hierarchical models for solving complex decision-making problems. Thus, this study aims to develop a readiness assessment method for implementation of Lean Construction using the GTA as a tool for its operationalization. As steps involved in building the method, it was carried out a literature review, in which it was possible to identify the readiness factors and sub-factors considered in the evaluation, and the parameterization of the model, through the establishment of inter-relations between the selected factors and sub-factors. The developed method was tested through the application in construction companies. As a result from the application, it was obtained the classification of two companies which showed insufficient and partial readiness levels. From the case studies, it was concluded that the proposed method is suitable for its purpose, meeting the criteria of feasibility, usability and utility. The method results allow to provide a diagnostic of the current situation of construction companies, which serves as a driver for change initiatives towards the Lean Construction.